2021
DOI: 10.1101/2021.06.22.449461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperactive WNT/CTNNB1 signaling induces a competing cell proliferation and epidermal differentiation response in the mouse mammary epithelium

Abstract: In the past forty years, the WNT/CTNNB1 signaling pathway has emerged as a key player in mammary gland development and homeostasis. While also evidently involved in breast cancer, much unclarity continues to surround its precise role in mammary tumor formation and progression. This is largely due to the fact that the specific and direct effects of hyperactive WNT/CTNNB1 signaling on the mammary epithelium remain unknown. Here we use a primary mouse mammary organoid culture system to close this fundamental know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(102 reference statements)
2
1
0
Order By: Relevance
“…5F ). In support, analogous phenotypes were recently observed in mammary organoid cultures treated with high-dose CHIR99021, a potent activator of the Wnt/β-catenin pathway ( Mourao et al, 2021 ). Based on our findings, we believe that constitutive Wnt activity in LC initially drives their conversion to basal-like cells, by repressing K8 expression and inducing basal traits such as K5/14, Id4 and p63 expression, and that they subsequently enter the same program of squamous transdifferentiation as mutant BC.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…5F ). In support, analogous phenotypes were recently observed in mammary organoid cultures treated with high-dose CHIR99021, a potent activator of the Wnt/β-catenin pathway ( Mourao et al, 2021 ). Based on our findings, we believe that constitutive Wnt activity in LC initially drives their conversion to basal-like cells, by repressing K8 expression and inducing basal traits such as K5/14, Id4 and p63 expression, and that they subsequently enter the same program of squamous transdifferentiation as mutant BC.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, our data showed that these early, b-catenin-induced changes to epithelial cell organization and behavior reflect the progressive transdifferentiation of mammary cells to an HF/epidermal-like fate, marked by the acquisition of HF and IFE marker expression (Figure 5F). In support, analogous phenotypes were recently observed in mammary organoid cultures treated with high-dose CHIR99021, a potent activator of the Wnt/b-catenin pathway (Mourao et al, 2021). Based on our findings, we believe that constitutive Wnt activity in LCs initially drives their conversion to basal-like cells, by repressing K8 expression and inducing basal traits, such as K5/14, Id4, and p63 expression, and that they subsequently enter the same program of squamous transdifferentiation as mutant BCs.…”
Section: Targeted Stabilization Of B-catenin To Luminal Mammary Cells...supporting
confidence: 83%
“…Different levels of Wnt/β-catenin signaling often result in the activation of distinct target genes which in turn determine different cell fates in a context-dependent manner (Matos et al, 2020;Mourao et al, 2021;Söderholm and Cantù, 2021). Our data suggest that Ascl4 expression may require high levels of Wnt/β-catenin activity.…”
Section: Discussionmentioning
confidence: 71%
“…Different levels of Wnt/β-catenin signaling often result in the activation of distinct target genes which in turn determine different cell fates in a context-dependent manner (Matos et al, 2020; Mourao et al, 2021; Söderholm & Cantù, 2021). Our data suggest that Ascl4 expression may require high levels of Wnt/β-catenin activity.…”
Section: Discussionmentioning
confidence: 99%